Transforming US intelligence for irregular war: Task Force 714 in Iraq - Shultz, Richard H. (Georgetown University Press, 2020)
Introduction : Task Force 714 and the Iraq War -- Adapting Intelligence for Twenty-First-Century Irregular Warfare -- From Hierarchy to Networks : The Empowerment of Armed Groups -- Transforming Intelligence Collection for Irregular War -- Transforming Intelligence Analysis for Irregular War -- Transforming Covert Paramilitary Operations for Irregular War -- Task Force 714 and the Sources of Transformation -- Epilogue : More Irregular War and the Challenge of Revisionist State Powers.